A Retrospective Cohort Study Characteristics of Chest X-Ray Findings in COVID-19 Patients that Presented to a Tertiary Care Facility in Dubai: Can a Severe Radiological Appearance Predict Clinical Outcome? - Duaa Yusuf Alhaddad; Ayeda Ahmed; Maryam Aldashtei; Ayoub Abedzadeh; Shaikh Sayeed Iqbal; Yaser Armaghan; Firas AlNajjar (Dubai Medical Journal)
Aim: We aimed to describe the most prominent features of COVID-19 on the chest X-ray (CXR) and to classify them using the radiographic assessment of lung edema (RALE) score. Furthermore, we aimed to correlate the RALE scores with clinically significant outcomes namely intensive care unit (ICU) admission and intubation from the emergency versus during hospital stay. In-hospital, death was studied as a secondary endpoint for severe RALE score. Materials and Methods: A retrospective cohort study was conducted on patients presenting to the emergency department (ED) of a tertiary hospital between the periods of March 2020 to August 2020. Included patients were symptomatic, COVID-19 positive by nasopharyngeal real-time polymerase chain reaction (RT-PCR), who also performed an initial CXR in the ED. Two experienced radiologists interpreted the CXRs and categorized them using RALE score into normal mild, moderate, and severe for further correlation with clinical endpoints. Results: From the 404 CXRs, most were categorized as mild and characteristically CXRs had bilateral lower and mid-zone ground-glass opacities. The frequency of intubation and ICU admission increased as the RALE score worsened with a statistically significant p value of <0.001. Severe CXR required earlier intervention and was found to have the highest proportion of mortality. Discussion: The RALE score has shown to be a highly reliable indicator for worse outcome in patients with acute respiratory distress syndrome. While RT-PCR has variable sensitivities, CXR has demonstrated to have characteristic findings and higher RALE scores having a significant correlation for intubation and ICU admission in this research. Conclusion: The prognostic utility of CXR in COVID-19 has been found to be of statistical significance for intubation and ICU admission. CXR is a simple, portable, and easy-to-disinfect method of evaluation that can be invaluable in determining timely intervention and disposition of patients expecting deterioration.